Bank efficiency and its relationship with stock performance: an estimation in Thailand - Nguyen, Thi Minh Ngoc (2013)
Using stochastic frontier analysis (SFA), the study investigates the alternative profit efficiency of 17 Thai banks listed in the stock exchange during the period from 2006 to 2012. In addition, the aim of paper is to evaluate the relevance and importance of efficiency level on the change in share performance. A mean profit efficiency score is about 80% throughout the sample. In the second step, efficiency change displays a negative impact on stock return, yet it fails to reflect the excess return on bank share in the augmented capital model. As a result, it seems to show that the efficiency score does not have an explanatory power on the stock return.